Noncanonical amino acids as prophage inducers for protein regulation in bacteria-based delivery systems - Hongfang Liu; Sijia Shen; Qi Xu; Yuyang Wang; Kejing Qi; Bowen Lu; Bing Tang; Min Wu; Fei Gan (mBio)
ABSTRACT Genetically engineered bacteria represent a promising drug delivery tool for disease treatment. The development of new strategies for specific and independent protein regulation is necessary, especially for combination protein drug therapy. Using the well-studied Escherichia coli phage λ as a model system, we applied noncanonical amino acids (ncAAs) as novel inducers for protein regulation in a bacteria-based delivery system. Screening the permissive sites of the Cro protein revealed that incorporation of AlocK at the K8 site with the MbPylRS-349F/tRNAPyl system produced a functional Cro-K8AlocK variant. Using an engineered λ lysogen expressing the MbPylRS-349F/tRNAPyl pair, Cro-8X, and the reporter mNeonGreen, in vitro and in vivo experiments showed that AlocK led to bacterial lysis through prophage activation and the release of mNeonGreen. If mNeonGreen was integrated into the λ prophage genome, λ phages released due to AlocK induction delivered the reporter gene into the recipient E. coli strain, enabling mNeonGreen expression. Furthermore, insertion of pIF at the F14 site with the AfpIFRS/tRNATyr pair produced a functional Cro-F14pIF variant. Importantly, AfpIFRS/tRNATyr and MbPylRS-349F/tRNAPyl pairs were confirmed to be mutually orthogonal. In a mixture of two engineered λ lysogens expressing different aaRS/tRNAs, Cro-ncAAs, and reporter proteins, AlocK and pIF independently induced bacterial lysis and activated the expression of mNeonGreen and mCherry in the recipient E. coli strain. Collectively, the proposed bacteria-based delivery system provides two options for protein delivery and enables independent regulation of multiple proteins with ncAAs, offering a novel approach for in situ protein regulation and combination therapy.IMPORTANCEThe use of genetically engineered bacteria as drug delivery vectors has attracted more and more attention in recent years. A key issue with bacteria-based delivery systems is how to regulate multiple protein drugs. Based on genetic code expansion technology, we developed a new strategy of using ncAAs as small molecular inducers for in situ protein regulation and engineered λ phage lysogen into a bacteria-based delivery system that can function in two delivery modes. Furthermore, this strategy enables independent regulation of multiple proteins by different ncAAs, offering important implications for combination therapy. This approach requires minimal genetic engineering efforts, and similar strategies can be applied to engineer other prophage-bacteria systems or study phage biology. This work expands the therapeutic applications of ncAAs and lysogenic phages.